Analisis Perilaku Periksa Payudara Sendiri (Sadari) dengan Pendekatan Teori Health Belief Mode di Wilayah Kerja Puskesmas Kandanghaur: Analysis of Breast Self-Examination Behavior (Sadari) Using the Health Belief Mode Theory Approach in the Kandanghaur Community Health Center Work Area - Nikita Amhely Claudya; Erna Widyastuti; Budi Astyandini (Universitas Ngudi waluyo, 2024)
Breast cancer is a malignant tumor that grows in the breast tissue, the most common organ malignancy in women. According to data from the Indramayu District Health Office in January-September 2022 as many as 3,824 women have had breast cancer screening, from the screening it was found that as many as 47 women had tumors or lumps in the breast, 33 women had the possibility of breast cancer, and 80 women were positive breast cancer. Based on a preliminary survey with village midwives and cadres in the working area of the Kandanghaur Health Center, it was found that there were 3 cases of breast cancer in the waterfall area. This research is an observational analytic study with a cross sectional approach. The population of this study were 227 women of childbearing age aged 20-35 years and a sample of 144 people and was taken using simple random sampling technique. The results of the univariate analysis of the chi-square test showed that perceived vulnerability was 65.3% high, perceived seriousness was 55.6% high, perceived benefits were high 57.6%, perceived barriers were high 65.0%. Bivariate analysis of perceived vulnerability (p value=0.000), perceived seriousness (p value=0.559), perceived benefits (p value=0.000) perceived obstacles (p value=0.017). The conclusion of the study is that there is a relationship between disease susceptibility, benefits and barriers to BSE practice behavior. Meanwhile, the perception of the seriousness of the disease has no relationship with BSE practice behavior. Suggestions for health workers to more often provide education on risk factors for breast cancer. Abstrak Dalam jaringan payudara keganasan organ yang paling sering terjadi pada wanita. Menurut data dari Dinas Kesehatan Kabupaten Indramayu pada bulan Januari-September tahun 2022 sebanyak 3824 wanita telah melakukan skrining kanker payudara, dari skrining tersebut didapatkan hasil bahwa sebanyak 47 wanita yang memiliki tumor atau benjolan pada payudara, 33 wanita kemungkinan kanker payudara, dan 80 wanita positif kanker payudara. Berdasarkan survei pendahuluan dengan Bidan Desa dan Kader di wilayah kerja Puskesmas Kandanghaur di dapatkan hasil bahwa di daerah curug terdapat 3 kejadian kanker payudara. Penelitian ini adalah penelitian analitik observasional dengan pendekatan cross sectional. Populasi penelitian ini yaitu wanita usia subur usia 20-35 tahun berjumlah 227 orang dan sampel 144 orang dan diambil menggunakan teknik simple random sampling. Hasil analisa univariat uji chi square persepsi kerentnan tinggi 65,3%, persepsi keseriusan tinggi 55.6%, persepsi manfaat tinggi 57,6%, persepsi hambatan tinggi 65,0%. Analisis bivariat persepsi kerentanan (p value=0,000), persepsi keseriusan (p value=0,559), persepsi manfaat (p value=0,000) persepsi hambatan (p value=0,017). Kesimpulan penelitian adalah ada hubungan antara kerentanan penyakit, manfaat dan hambatan dengan perilaku praktik SADARI. Sedangkan persepsi keseriusan penyakit tidak memiliki hubungan dengan perilaku praktik SADARI. Saran bagi tenaga kesehatan agar lebih sering memberikan edukasi faktor resiko terjadinya kanker payudara.